Protocol publication rate and comparison between article, registry and protocol in RCTs - Sylvain Mathieu; Jean-Baptiste Bouillon-Minois; Laurent Renard Triché; Emmanuel Coudeyre; De Chazeron Ingrid; Finotto Thomas; Catherine Laporte; Xavier Moisset; Ludovic Samalin; Guillaume Villatte; Bruno Pereira; Methodology And Evidence Statistics for Transparency in medical Research and Outcome reporting (MAESTRO) working group (BMC Medical Research Methodology)
Abstract Background Increasing transparency in clinical research is crucial to avoid misleading conclusions. Registering clinical trials prior to participant enrolment is mandatory, and the publication of trial protocols could further enhance transparency. However, the impact of protocol publication on primary outcomes (PO) and sample sizes (SS) remains unclear. This study aimed to determine the rates of trial protocol publication and registration for a sample of randomized controlled trials (RCTs) and to compare the consistency of published and registered PO and SS. Methods A search was conducted in MEDLINE via PubMed® for RCT reports indexed in May and June 2023 across various medical specialties, focusing on general and high-impact factor journals. Data were extracted regarding trial registration, protocol publication, and comparisons were made between PO and SS in articles, registries, and published protocols. Results Out of 1119 references, 589 (52.6%) were RCTs. The corresponding protocol was published for 146 RCTs (24.8%) including 40 over 140 (28.6%) (6 without end date available) after the trial had ended. Sixty-two (42.4%) protocols were published before the trial conclusion, with no significant differences between PO and SS in published protocols and their corresponding articles. Five hundred and twenty-eight (89.6%) RCTs were registered, 225 over 510 (44%) were registered before the study start with no differences in PO and SS between article and registry. Articles published in generalist or high impact factor journals were associated with higher frequencies of published protocols and trial registration and a lower frequency of difference in PO and SS between articles, registries, and published protocols. Conclusions While publishing trial protocols may enhance transparency in peer-review process, the initial registered protocol alone appears sufficient for ensuring consistency in primary outcomes and sample sizes. Protocol publication does not seem to provide additional significant benefits in terms of outcome reporting.